Leisure time physical activity among Brazilian adults: National Health Survey 2013 and 2019 - Gregore Iven Mielke; Sheila Rizzato Stopa; Crizian Saar Gomes; Alanna Gomes da Silva; Francielle Thalita Almeida Alves; Maria Lúcia França Pontes Vieira; Deborah Carvalho Malta
ABSTRACT Objective: The aim of this study was to analyze the prevalence of leisure-time physical activity in 2013 and 2019 according to sociodemographic characteristics in Brazilian adults. Methods: We analyzed data from the National Health Surveys conducted in 2013 and 2019. Prevalence of leisure-time physical activity (150+ minutes per week in physical activities) was calculated according to gender, age, education, race/skin color, Federative Units, and regions of Brazil in 2013 and 2019. Poisson regression models and 95% confidence intervals (95%CI) were used to compare leisure-time physical activity across different groups in 2013 and 2019. Results: The proportion of Brazilian adults active in leisure-time increased from 22.7% (95%CI 22.06-23.34) in 2013 to 30.1% (95%CI 29.44-30.67) in 2019. The prevalence of leisure-time physical activity increased between 2013 and 2019 in 23 of the 27 Federative Units in Brazil. Both in 2013 and in 2019, the proportion of active people during leisure time was higher in men, young people, with a high level of education and individuals with white skin color. Overall, the magnitude of the observed differences in leisure-time physical activity between sociodemographic groups slightly decreased from 2013 to 2019. Conclusions: Despite the increase in the prevalence of leisure-time physical activity among Brazilian adults in the last six years, marked sociodemographic inequalities persist. The success of future public policies to promote physical activity in leisure must be evaluated from the perspective of social determinants of health and the reduction of inequalities in the practice of physical activity.